Potential of Single Garlic to Prevent Pro Inflammatory Macrophage and Inflammation in HFD Mice - Putri Diyah Anggraini; Miftahul Mufinadiroh; Hendra Susanto; Betty Lukiati; Sri Rahayu Lestari (Journal of Tropical Life Science, 2022)
A high-fat-enriched diet causes an increase in the level of oxidized LDL (Ox-LDL) in the blood. The presence of Ox-LDL will activate macrophages to secrete pro-inflammatory cytokines and lead to severe inflammation. Single bulb garlic has a potential anti-inflammatory effect due to of high-fat diet. This research aimed to investigate the effect of single bulb garlic extract (SBGE) on the pro-inflammatory cytokines TNF-Î± (CD11b+TNF-Î±+) and IL-1b (CD11b+IL-1b+) in the spleen, spleen weight, and TNF-Î± secretion in HFD mice. Twenty-four mice were divided into six groups: normal (healthy mice); HFD (HFD mice without any treatment); HFD + Simvastatin (HFD mice receiving simvastatin); HFD + SBGE 100; HFD + SBGE 200; and HFD + SBGE 400 (HFD mice receiving 100, 200, and 400 mg/kg BW of SBGE for 4 weeks). Blood serum was collected at the end of treatment, and macrophage was isolated from the spleen. The relative number of CD11b+TNF-Î±+ and CD11b+IL-1b+ were examined using flow cytometry. SBGE treatment significantly (p<0.05) reduced the spleen weight and the relative number of CD11b+TNF-Î±+ and CD11b+IL-1b+ in the spleen of HFD mice. SBGE treatment also prevents the elevation of TNF- Î± levels in the blood serum. The optimal dose of SBGE to diminish the relative number of CD11b+TNF-Î±+, CD11b+IL-1b+ in the spleen, and TNF-Î± in the serum was 100 mg/kg BW.